Pengaruh Labelisasi Halal, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Tteoboki: Studi Kasus Pada Konsumen Kims Tapokki - Anti, Risti; Siahaan, Rumiris; Cahyadi, Lukieto; Napitu, Resna (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to determine the Effect of Halal Labeling, Price and Product Quality on Tteokbokki Purchase Decisions (Case Study on Consumers of Kims Tapokki). This type of research is a quantitative method approach, sampling technique using accidental sampling technique and data collection by distributing questionnaires to 96 respondents Kims Tapokki. While the method of data analysis using multiple linear regression analysis.From the results of this test, it can be concluded that based on the results of the analysis of hypothesis 1, it can be seen that tcount (2.181) > ttable (1.985), as well as the significance value of 0.032<0.05, it can be concluded that the first hypothesis is accepted, meaning Halal Labeling (X1 ) affects the Purchase Decision (Y), hypothesis 2 can be seen that tcount (3.837) > ttable (1.985), and the significance value is 0.000 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the price (X2) affects the Purchase Decision. (Y), hypothesis 3 can be seen that tcount (8.455) > ttable (1.985), and the significance value is 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that Product Quality (X3) has an effect on Purchase Decision (Y), and hypothesis 4 it can be seen that Fcount (82.434) > Ftable (2.70), and a significance value of 0.000 <0.05, it can be concluded that the fourth hypothesis is accepted, meaning Labelis Halal ation (X1), Price (X2), and Product Quality (X3) have a joint (simultaneous) effect on Purchase Decision (Y).